2017
DOI: 10.18632/oncotarget.16361
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of HSF1 at serine 326 residue is related to the maintenance of gynecologic cancer stem cells through expression of HSP27

Abstract: Cancer stem-like cells (CSCs)/ cancer-initiating cells (CICs) are defined by their higher tumor-initiating ability, self-renewal capacity and differentiation capacity. CSCs/CICs are resistant to several therapies including chemotherapy and radiotherapy. CSCs/CICs thus are thought to be responsible for recurrence and distant metastasis, and elucidation of the molecular mechanisms of CSCs/CICs are essential to design CSC/CIC-targeting therapy. In this study, we analyzed the molecular aspects of gynecological CSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 51 publications
3
49
0
Order By: Relevance
“…The upstream transcription factor of HSP27 is heat shock factor-1 (HSF1) which could be activated by phosphorylation at the serine 326 residue (pSer326) in CSCs/CICs, and the evidence of phosphorylation at pSer326 is considered to be necessary for induction of HSP27. In this very recent paper [62], using human ovarian cancer samples, the authors showed that higher expressions of HSF1 pSer326 and hence transcription of HSP27 is associated with the survival of the CSCs/CICs in these samples. The authors also noted that in the in vitro experiment, both down-regulation and overexpression of HSF1 affect cancersphere-formation under non-stress conditions.…”
Section: Typical Examples Of Anti-cancer Effects Of Mild Hyperthermiamentioning
confidence: 97%
See 3 more Smart Citations
“…The upstream transcription factor of HSP27 is heat shock factor-1 (HSF1) which could be activated by phosphorylation at the serine 326 residue (pSer326) in CSCs/CICs, and the evidence of phosphorylation at pSer326 is considered to be necessary for induction of HSP27. In this very recent paper [62], using human ovarian cancer samples, the authors showed that higher expressions of HSF1 pSer326 and hence transcription of HSP27 is associated with the survival of the CSCs/CICs in these samples. The authors also noted that in the in vitro experiment, both down-regulation and overexpression of HSF1 affect cancersphere-formation under non-stress conditions.…”
Section: Typical Examples Of Anti-cancer Effects Of Mild Hyperthermiamentioning
confidence: 97%
“…These results indicate that HSF1 has a role in the maintenance of CSCs/CICs independent of stress, when these cells are matured. Based on the discussed in Section 2.8, HSF1 is only responsible for the transcription of the inducible HSPs, such result in [62] is surprising, and deserves re-confirmation and further study of similar experiments, to find On the other hand, the tumor-suppressor LKB1, which encodes a serinethreonine kinase, directly phosphorylates and activates the 5' adenosine monophosphate-activated protein kinase (AMPK), which is a central metabolic sensor. AMPK regulates lipid, cholesterol and glucose metabolism in liver, muscle and adipose tissue [63].…”
Section: Typical Examples Of Anti-cancer Effects Of Mild Hyperthermiamentioning
confidence: 98%
See 2 more Smart Citations
“…Numb‐1‐ and Notch‐specific T‐cells eliminated luminal CSC/TIC‐like cells in a breast cancer model . In a gynaecological cancer (endometrioid adenocarcinoma), ALDH high cells preferentially expressed Hsp27, the over‐expression of which is associated with poor prognosis . Mitogen‐activated kinase (MAPK)13, pituitary tumour‐transforming gene protein‐binding factor (PTTG1IP), calpain 1 (CAPN1) and ubiquilin 2 (UBQLN2) were also found highly expressed in these cells compared with that in ALDH low cells .…”
Section: Potential Immune Targeting Of Cscs/ticsmentioning
confidence: 99%